HUBUNGAN KEAKTIFAN PENGURUS ORGANISASI SISWA INTRA SEKOLAH (OSIS) DALAM PELAKSANAAN KEGIATAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) DENGAN HASIL BELAJAR PADA MATA PELAJARAN SEJARAH DI SMAN 1 SINGKEP - A Fathisra Alawiya A; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: SMAN 1 Singkep officially established on January 1, 1969 with sk Mendikbud 28 May 1969 Number 83/UKK/3/1969. This research aims (1) to find out the work program created by the administrator of Sma Negeri 1 Singkep, (2) To know the activeness of the student council in carrying out the student council activities in SMAN 1 Singkep, (3) To know the results of studying student council in historical subjects in SMAN 1 Singkep, (4) To know the activeness of the Student Council Administrator in the Implementation of Student Council Activities With The Results of Learning On Historical Subjects in SMAN 1 Singkep. The research approach used in this study is quantitative research by survey method, using simple linear regression analysis. The subject of this study was the student council of SMAN 1 Singkep which numbered 40 students. The criterion of the degree of coefficient relationship is 0. 153,meaning the activeness of the student council in the implementation of student council activities has a low relationship due to what is the value of pearson corelation 0.21-0.40. The higher the activeness of student council administrators in the implementation of student council activities,the higher the learning results of students in SMAN 1 Singkep. Based on a simple linear regression analysis known as a positive value regression coeffesien with the regression equation Y = 67.786 + 0.477X, meaning the activeness of the student council in the implementation of student council activities (X) has a positive effect on the study results (Y). The value of t count = 2.624 > 0.3120 = t table, so itcan be concluded that H0 is rejected, which means that